MEMBANGUN APLIKASI TES IQ PENERIMAAN MAHASISWA BARU PADA SMARTPHONE BERBASIS ANDROID - Ertina Sabarita Barus; Oktrine Rohliharni Purba (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
Before taking an IQ test officially, individuals often use media books or websites to do IQ test exercises. Lately, smartphone media has been very popular with users in supporting information technology. To accommodate smartphone facilities, the author will apply for an IQ Test. New Student Admission based on Android. The software used to make this application is Android Studio. This IQ test application is used using the Android operating system used on Android-based smartphones in the Java programming language.